2013
DOI: 10.14221/ajte.2013v38n3.3
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Teach English Language in the Practicum: What Challenges do Non-Native ESL Student Teachers Face?

Abstract: This study investigates the challenges sixteen nonnative preservice ESL teachers in a Bachelor of Education (English

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 28 publications
9
59
2
1
Order By: Relevance
“…Emotional and pedagogical support are also stressed because 82.25% of respondents appreciated that their mentors showed trust, support and genuine concern for their professional development which confirms that their school mentors' personal and professional qualities are highly valued (statement 5). The problems identified related to their 'emotional and psychological stress' when learning to teach within school settings are also discussed in Wang & Odell (2002) and Gan (2013). Likewise, 80% of respondents recognized the importance of the effort made by mentors in ensuring that their verbal messages were clearly understood by their mentees (statement 6).…”
Section: Quantitative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emotional and pedagogical support are also stressed because 82.25% of respondents appreciated that their mentors showed trust, support and genuine concern for their professional development which confirms that their school mentors' personal and professional qualities are highly valued (statement 5). The problems identified related to their 'emotional and psychological stress' when learning to teach within school settings are also discussed in Wang & Odell (2002) and Gan (2013). Likewise, 80% of respondents recognized the importance of the effort made by mentors in ensuring that their verbal messages were clearly understood by their mentees (statement 6).…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…However, as Mai & Baldauf (2010) argued, what student teachers have learned in university training rooms may be in conflict with the reality of classrooms, particularly with what they see and what they are expected to do in practice. The study reported by Gan (2013) suggests that putting theory into classroom practice involves an enormous challenge during the practicum experience characterized by a 'reality shock'. Bridging the gap between theory and practice has always been a matter of profound discussion in the professional preparation of all language teachers, becoming a highly controversial issue in the field of second language education (Wallace, 1996;Farrell, 1998;Cheng et al, 2010).…”
Section: Integration Of Theory and Practicementioning
confidence: 99%
See 1 more Smart Citation
“…This lack of theorisation is one of the reasons why there is inconsistency between studies in terms of what constitutes the context. While some researchers consider the context as the community involved in the teaching and learning activity (e.g., Atay, 2007;Brandt, 2006;de Courcy, 2011;Gan, 2013;Trent, 2013;Urzúa & Vásquez, 2008;Yuan & Lee, 2014), others account for the systems of rules (Atay, 2007;Engin, 2014;Gao & Benson, 2012) and pedagogical tools (de Courcy, 2011;Johnson & Dellagnelo, 2013). As what constitutes context of teaching and learning varies from one study to another, it is really challenging to synthesise and compare findings from different studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there remains a lack of a comprehensive view of the teacher as a learner of teaching. Despite commonly studying teachers' professional learning, a number of studies look into their cultural backgrounds (e.g., Gan, 2013;Gao & Benson, 2012;Miller, 2007;Nemtchinova, 2005), while others investigate prior beliefs (e.g., Le, 2014;Mak, 2011;Ng, Nicholas, & Williams, 2010;Tang, Lee, & Chun, 2012;Yuan & Lee, 2014), emotions (e.g., Atay, 2007;Benson, 2012;Brandt, 2006;Farrell, 2008;H. T. M. Nguyen, 2010;Pillen, Beijaard, & den Brok, 2013;Trent, 2013), and professional identity (e.g., Haniford, 2010;Miller, 2007;Trent, 2011Trent, , 2013.…”
Section: Contemporary Research On L2 Teacher Learning In Light Of Thementioning
confidence: 99%